Financial development, real sector and economic growth: Evidence from emerging market economies. (1st September 2020) - Raghutla, Chandrashekar; Chittedi, Krishna Reddy
Abstract: There is a developing concern among developed, developing, and emerging economies in relevance to increasing real sector expenditure across the world. As a result, all countries have started to increase their real sector expenditure by increasing the share of finance. Hence, this study aims to examine the effects of both financial development and real sector on economic growth; we choose five emerging market economies to explain the economic growth process between 2000 and 2016. The results of long‐run elasticities document that real sector and financial development play a significant role in promoting economic growth. The results also suggest that money supply, exchange rate and inflation have a considerable positive effect on economic growth, respectively. Given these findings, we suggest that both governments and policy makers of the BRICS nations to initiate more effective policies to increase the real sector expenditure and develop financial sector. The increasing real sector will allow the economies to grow further by ensuring sustainable economic development across the BRICS member countries.